Lipoma-like hibernoma: an atypical lipoma/well-differentiated liposarcoma mimicker - Reis-Filho Jorge S.; Cruz João; Valbueva Carmen Ruiz de; Schmitt Fernando C. (Sociedade Brasileira de Patologia Clínica, 2002)
Hibernomas are benign lipomatous tumors which show differentiation toward brown fat. Recently, unusual variants have been described, including myxoid, spindle cell, and lipoma-like variants. Lipoma-like hibernoma (LLH) is characterized by mature univacuolated adipocytic cells with rare admixed multivacuolated brown fat-like cells, which may resemble lipoblasts, leading to a misdiagnosis of atypical lipoma/well-differentiated liposarcoma (AL/WDLS). We herein report a case of LLH arising on the anterior aspect of the left thigh of a 17-year-old female. A marginal excision was performed. The patient was discharged and remains well four months after surgery. Histological examination showed a lobulated neoplasm composed of univacuolated mature adipose cells admixed with small vessels and occasional mast cells. Scattered islands of brown fat-like cells accounting for less than 10% of the neoplasm were found. Sometimes these cells presented indented and scalloped nuclei, resembling lipoblasts. A final diagnosis of LLH was made based on the presence of focal areas with typical hibernoma morphology, and the lack of atypical hyperchromatic stromal cells. Pathologists must be aware of the typical histological findings of LLH, not to confuse it with AL/WDLS.